2023
DOI: 10.17261/pressacademia.2023.1674
|View full text |Cite
|
Sign up to set email alerts
|

ESG scores relationship with firm performance: panel data evidence from the European tourism industry

Abstract: Purpose – This paper aims to investigate if there is a significant relationship between corporate ESG (environmental, social, and governance) scores and firm profitability (ROA) and whether this relationship is positive, negative, or neutral. Methodology – The study examines all listed companies from the European tourism industry for which ESG scores are available. The final sample consists of 48 firms from 14 European countries and 258 firm-year observations, obtained through the Refinitiv database for the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The findings showed contradicting results due to the firm's size being measured by the total assets using the historical value compared to the Tobin's Q, ROA, and ROE that were measured by the market price. Our result is consistent with Demiraj et al (2023) who also found a negative relationship between firm size and firm performance. Moreover, the current ratio (CR) also showed a negative and significant relationship at 10% and 5% on Tobin's Q and ROE, respectively.…”
Section: Empirical Regression Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The findings showed contradicting results due to the firm's size being measured by the total assets using the historical value compared to the Tobin's Q, ROA, and ROE that were measured by the market price. Our result is consistent with Demiraj et al (2023) who also found a negative relationship between firm size and firm performance. Moreover, the current ratio (CR) also showed a negative and significant relationship at 10% and 5% on Tobin's Q and ROE, respectively.…”
Section: Empirical Regression Resultssupporting
confidence: 93%
“…However, firm growth (GROWTH) held the same finding from the main analysis, showing a positive and significant relationship at 1% and 5% on ROA and ROE, respectively. Our additional findings offer evidence of the ESG pillars on market and accounting-based performance in Malaysia since Carnini Pulino et al (2022) and Demiraj et al (2023) only focused on the effects of ESG on the ROA and EBIT. Note: The reported t-statistics are in parentheses.…”
Section: Empirical Regression Resultsmentioning
confidence: 76%